10.1016/s1544-8800(05)70429-2 (CrossRef Listing of Deleted DOIs, 2000)
Traditional Chinese medicine (TCM) has a long-standing history in the treatment of rheumatoid arthritis (RA), known as "Bi Zheng," and offers a comprehensive therapeutic approach characterized by multi-target and multi-pathway mechanisms. Modern pharmacological research has demonstrated that bioactive compounds and herbal formulas derived from TCM (e.g., triptolide [TPL] from Tripterygium wilfordii and the Xinfeng Capsule [XFC]) effectively interfere with the complex pathogenesis of RA. These interventions modulate diverse pathological processes, including the suppression of pro-inflammatory cytokines (e.g., TNF-α, IL-6, and IL-1β), induction of apoptosis in hyperplastic synovial cells, and regulation of novel cell death pathways (such as ferroptosis and pyroptosis). Furthermore, TCM components exhibit potent antioxidant properties, inhibit pathological angiogenesis, ameliorate hypercoagulable states, and restore gut microbiota dysbiosis, which is increasingly recognized as a key environmental factor in RA development. Notably, emerging evidence highlights the critical role of non-coding RNAs (ncRNAs) as mediators of these therapeutic effects. Concurrently, a growing body of clinical evidence from randomized controlled trials (RCTs), cohort studies, and real-world data mining consistently confirms the significant efficacy and safety of TCM interventions in relieving RA symptoms, improving joint function, and reducing disease activity. By integrating preclinical and clinical findings, a robust evidence chain emerges, validating traditional TCM concepts through modern scientific rigor. Therefore, TCM represents a valuable resource for RA drug discovery and integrative treatment strategies. Further in-depth investigation is needed into its specific molecular targets, optimal formulations, and long-term clinical outcomes to facilitate its global translation and application.